A Closure Approximation for the Nonstationary M/M/s Queue - Rothkopf, Michael H.; Oren, Shmuel S. (Management Science, 1979)
Typical queues do not have constant arrival rates. This paper discusses effective computational methods for dealing with queues having nonstationary arrival processes. It presents a computationally undemanding approximate method for finding the time dependent mean and standard deviation of the number of customers in an s server queueing system with time-varying arrival and service rates. Results are exhibited for various 1 and 3 server queues with constant service rates and sinusoidal components in the arrival rate.